Molecular and Transmission Characteristics of Mycobacterium Tuberculosis Strains Among College Students in Beijing, China - Cao X; Li X; Song Z; He P; Zhang R; Teng C; Sun Q; Wang X; Zhao B; Zhang Z; Zhao Y (Infection and Drug Resistance)
Xiaolong Cao,1,2,* Xinyue Li,1,3,* Zexuan Song,4 Ping He,5 Ruiqing Zhang,1,3 Chong Teng,6 Qian Sun,2 Xue Wang,2 Bing Zhao,3 Zhiguo Zhang,7 Yanlin Zhao3 1National Institute for Communicable Disease Control and Prevention, Chinese Center for Disease Control and Prevention, Beijing, 102206, People’s Republic of China; 2Outpatient Department, Beijing Changping Institute for Tuberculosis Prevention and Treatment, Beijing, 102200, People’s Republic of China; 3National Tuberculosis Reference Laboratory, Chinese Center for Disease Control and Prevention, Beijing, 102206, People’s Republic of China; 4Department of Clinical Laboratory, Children’s Hospital, Capital Institute of Pediatrics, Beijing, 100020, People’s Republic of China; 5Center for Infection Biology, School of Medicine, Tsinghua University, Beijing, 100084, People’s Republic of China; 6Tuberculosis Prevention and Control Department, Beijing Dongcheng District Center for Disease Control and Prevention, Beijing, 100050, People’s Republic of China; 7Hospital Management Office, Beijing Changping Mental Health Care Hospital, Beijing, 102202, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiguo Zhang, Beijing Changping Mental Health Care Hospital, Changping District, Beijing, 102202, People’s Republic of China, Email zhgzh8689@126.com Yanlin Zhao, National Tuberculosis Reference Laboratory, Chinese Center for Disease Control and Prevention, Changping District, Beijing, 102206, People’s Republic of China, Email zhaoyl@chinacdc.cnBackground: College students are a crucial link in curbing the epidemic. The aim of this study is to analyze the genetic diversity and drug resistance of Mycobacterium tuberculosis strains in college students with tuberculosis in Beijing, revealing the lineage structure and transmission patterns specific to this group.Methods: This study used the hospital’s electronic management system to screen for tuberculosis among college students in Changping District, Beijing, from January 2004 to December 2023. Socio-demographic and clinical data were collected, and whole-genome sequencing was performed on culture-positive isolates. Isolates with a genetic distance of less than 12 SNPs were grouped into the same genomic cluster. The TB Profiler software predicted drug resistance mutations, and categorical data were analyzed using Chi-square or Fisher’s exact tests.Results: Among the 1436 college students with tuberculosis, a total of 153 isolates successfully underwent whole-genome sequencing. The results showed that about one-third (49/153) of the isolates carried one or more drug resistance genes, with more than half (26/49) associated with first-line anti-tuberculosis drugs. However, encouragingly, the incidence of drug-resistant tuberculosis showed a significant downward trend, with statistical significance (p< 0.05). Lineage 2 (86.3%, 132/153) was the predominant genotype, with the Beijing genotype (90.1%, 120/153) being the most common, while the isolation of Lineage 3 in a student from Xinjiang. Sixteen college student isolates clustered, and all of which were Beijing genotype. Transmission within the same campus showed characteristics of short clustering time.Conclusion: The drug resistance rate among college students is relatively high, however it shows a declining trend. School tuberculosis infections could stem not only from within-campus transmission but also necessitate consideration of spatial and cross-regional spread possibilities.Keywords: Mycobacterium tuberculosis, whole genome sequencing, lineage, transmission, drug resistance, college students